2019
DOI: 10.5004/dwt.2019.24109
|View full text |Cite
|
Sign up to set email alerts
|

Removal of cephalexin from artificial wastewater by mesoporous silica materials using Box-Behnken response surface methodology

Abstract: a b s t r a c tMesoporous silica such as MCM-41 was used as an adsorbent for the removal of cephalexin antibiotic from synthetic wastewater. In this study, MCM-41 adsorbent was synthesised and was characterised by FE-SEM, XRD, FTIR and isotherms of adsorption/desorption of N 2 . The effects of initial pH, adsorbent dose, initial adsorbate concentration, contact time and temperature on process efficiency were evaluated using Box-Behnken statistical experiment design (RSM). FTIR analysis revealed the Si-OH, H-O-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…However, 60 min was enough to achieve more than 80% of the CFX removal. Panahi et al [27] reported that the optimal removal of CFX (90%) by mesoporous silica materials was recorded with pH 3, 800 mg/L of the adsorbent dose, for 50 mg/L of CFX at 40 • C, and after 30 min. Initial CFX concentration (10-50 mg/100 mL) (x 1 ), APJAP dosage (3-10 mg/100 mL) (x 2 ), time (10-60 min) (x 3 ), and pH (4-9) (x 4 ).…”
Section: Optimization and Deep Learning Studymentioning
confidence: 99%
“…However, 60 min was enough to achieve more than 80% of the CFX removal. Panahi et al [27] reported that the optimal removal of CFX (90%) by mesoporous silica materials was recorded with pH 3, 800 mg/L of the adsorbent dose, for 50 mg/L of CFX at 40 • C, and after 30 min. Initial CFX concentration (10-50 mg/100 mL) (x 1 ), APJAP dosage (3-10 mg/100 mL) (x 2 ), time (10-60 min) (x 3 ), and pH (4-9) (x 4 ).…”
Section: Optimization and Deep Learning Studymentioning
confidence: 99%
“…The presence of calcium ions increases the adsorption rate at pH values higher than 4.5 owing to the formation of ternary complexes through calcium-bridging. However, compared with other adsorptive materials, MCM-41 still has a low capacity of removing antibiotics from wastewaters, which suggests the need for further research and investigations [ 199 ]. Moreover, the adsorption capacity of ciprofloxacin hydrochloride using an iron-modified MCM-41 was investigated.…”
Section: Application Of Mesoporous Silica Nanoparticlesmentioning
confidence: 99%
“…Currently, various biological and physicochemical methods have been employed for pollutant removal, including advanced oxidation, biodegradation, adsorption, and flocculation. The complete degradation and oxidation of HA is difficult because of the refractory character. Among these methods, adsorption is the most common method used for contaminant removal in the wastewater treatment process with the advantages of no potential secondary pollutants, efficient removal rate, and simple technical requirement. …”
Section: Introductionmentioning
confidence: 99%